2012
DOI: 10.1002/jez.1722
|View full text |Cite
|
Sign up to set email alerts
|

David and Goliath: A Mitochondrial Coupling Problem?

Abstract: An organism's size, known to affect biological structures and processes from cellular metabolism to population dynamics, depends upon the duration and rate of growth. However, it is still poorly understood how mitochondrial function affects the energetic basis of growth, especially in ectotherms, which represent a huge majority of animal biodiversity. Here, we present an intraspecies comparison of neighboring populations of frogs (Rana temporaria) that have large differences in body mass even at the same age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 48 publications
(68 reference statements)
3
32
1
Order By: Relevance
“…The respiratory control ratios (RCRs) were significantly different between species and were significantly dependent on M b (Table 1). Importantly, mean RCR values obtained (3.2±0.1) in this study fall within the range of values previously published for ectotherm liver mitochondria respiring on succinate (1.4 to 5.8; Akhmerov, 1986;Brand et al, 1991;Hulbert et al, 2002;Savina et al, 2006;Salin et al, 2012b). Calculated fractional mitochondrial aerobic scope (fAS m ) was significantly higher in larger individuals (Table 1), with a significant dependence on M b (fAS m =2.4×M b 0.14 , where M b is in g; R 2 =0.28, P<0.001).…”
Section: B and Liver Masssupporting
confidence: 91%
See 4 more Smart Citations
“…The respiratory control ratios (RCRs) were significantly different between species and were significantly dependent on M b (Table 1). Importantly, mean RCR values obtained (3.2±0.1) in this study fall within the range of values previously published for ectotherm liver mitochondria respiring on succinate (1.4 to 5.8; Akhmerov, 1986;Brand et al, 1991;Hulbert et al, 2002;Savina et al, 2006;Salin et al, 2012b). Calculated fractional mitochondrial aerobic scope (fAS m ) was significantly higher in larger individuals (Table 1), with a significant dependence on M b (fAS m =2.4×M b 0.14 , where M b is in g; R 2 =0.28, P<0.001).…”
Section: B and Liver Masssupporting
confidence: 91%
“…Such a difference in mitochondrial coupling efficiency has previously been shown to correlate with intraspecific variation in M b in natural populations of common frogs (Salin et al, 2012b). It has been suggested that a change in mitochondrial membrane proton leak is one of the underlying biochemical mechanisms involved in the variability of mitochondrial efficiency in common frogs (Salin et al, 2012b). To support this, we have found that there is a strong negative correlation between proton conductance and M b , similar to previous studies on avian and mammalian liver mitochondria (Porter and Brand, 1993;Brand et al, 2003).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations